Joint Production Cost Allocation in Determining Cost of Goods Production to Optimize Profits - Mutiara Sari, Vira; Supriati, Diana (Research of Accounting and Governance, 2024)
PT Kemang Food utilizes the selling price method and the average per unit method for allocating joint production costs to its main products and by-products. The company produces sausages, burgers, delicatessen, meatballs, and a by-product consisting of beef and MDM (Mechanically Deboned Meat) from chicken esophagus, breastbone, and thigh. The study reveals that, according to the profit achievement policy and the targeted cost calculation, the selling price method is more profitable than the average per unit method. The profit obtained through the selling price method exceeds that of the average per unit method. Despite this, both methods experienced a decline in profits in 2020 due to the COVID-19 pandemic, as evidenced by trend analysis. Managerial implications stress the significance of accurate cost determination for optimizing company profits, especially during challenging times such as the pandemic. This underscores the need for adaptability in cost allocation strategies to maintain financial health and achieve optimal production costs in the face of external disruptions. The findings emphasize the importance of strategic decision-making in managing joint production costs for sustainable profitability